2001
DOI: 10.1111/j.1524-475x.2001.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychoneuroimmunological Outcomes in Dementia Caregiver Intervention Studies: An Idea Whose Time Has Come?

Abstract: Volume 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…Other studies found that stroke caregiver perceptions of their own health worsened over the course of providing care 8,9. Because insufficient attention has been given to the health status and health promotion activities of family caregivers,10,13,18,76,77 further enhancement of the TASK intervention to address these areas in stroke caregivers is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that stroke caregiver perceptions of their own health worsened over the course of providing care 8,9. Because insufficient attention has been given to the health status and health promotion activities of family caregivers,10,13,18,76,77 further enhancement of the TASK intervention to address these areas in stroke caregivers is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the literature on informal ADRD caregiving intervention studies employing biobehavioral measures is limited, at best. In 2001, Farran and colleagues published a call-to-action in their review paper, requesting interdisciplinary researchers to combine their collaborative efforts to pursue ADRD intervention research, investigating neuroendocrine and immune outcomes [24]. Based on our review, in the two decades since Farran et al (2001), only fourteen studies followed their recommendations to include biological outcomes in ADRD caregiving intervention study designs.…”
Section: Limited Biobehavioral Scope Of Existing Ad Informal Caregivi...mentioning
confidence: 99%
“…In 2001, Farran and colleagues published a call-to-action in their review paper, requesting interdisciplinary researchers to combine their collaborative efforts to pursue ADRD intervention research, investigating neuroendocrine and immune outcomes [24]. Based on our review, in the two decades since Farran et al (2001), only fourteen studies followed their recommendations to include biological outcomes in ADRD caregiving intervention study designs. Thus, in this systematic review article, we aim to (1) review the limited existing studies, which assessed the impact of ADRD informal caregiving interventions on neuroendocrine, immune, and psychophysiological parameters and (2) summarize the current state of the literature.…”
Section: Limited Biobehavioral Scope Of Existing Ad Informal Caregivi...mentioning
confidence: 99%